Persepsi Orang Tua Terhadap Proses Bimbingan Belajar Anak Di Rumah - Suwarto Suwarto; Hulman Fajri (Universitas Indraprasta PGRI Jakarta, 2018)
Perception is always related to the symptoms and experience. The more experience and knowledge a person gains, the more and more perceptions he has. In addition to science and experience, perceptions are also influenced by factors of needs and psychology. Thus, one's perception of education differs from one another. This research aims to explain the perceptions of parents in the process of child counseling at home. It is a qualitative research using data reduction, data presentation, conclusion and verification. The results of this research are poorly educated parents just pay little attention to the student’s learning guidance at home, resulting in many students showing little learning interest and dropping out of school. Students with highly educated parents are more lucky because the learning guidance can be obtained from their parents at home even though their parents’s activities at times become constraints.